Residue depletion profile and withdrawal interval estimation of ivermectin in eggs following topical administration of injectable ivermectin to domestic chickens (Gallus domesticus): a pilot study - Mercer, Melissa A.; Davis, Jennifer L.; Wetzlich, Scott E.; Clapham, Maaike O.; Tell, Lisa A. (Frontiers in Veterinary Science, 2025)
IntroductionTopical ivermectin is commonly prescribed extra-label for the control of mite infestations in backyard chicken flocks in the US.MethodsDomestic laying hens (n = 8; 78 weeks of age, weight 1.7–2.2 kg) were administered injectable ivermectin solution topically over the jugular vein (0.4 mg/kg every 7 days for 2 doses). Ivermectin concentrations in egg white and egg yolk were determined using UPLC with fluorescence detection.ResultsThe average period between eggs laid was 1.52 days. Ivermectin preferentially distributed to the egg yolk with an observed Cmax of 3.54 ng/g occurring at observed Tmax of 6.6 days and a T1/2 of 9.5 days. Residues persisted at low concentrations in egg yolk for up to 71 days after the final dose. WDIs for the egg yolk matrix were estimated using the FDA, EMA, and terminal-elimination half-life multiplier methods (HLM). The longest estimated WDI was 102 days for the EMA 95/95 method (95% confidence interval for 95th population percentile) with the limit of detection (LOD; 0.03 ng/g) set as the maximum residue limit. The FDA 95/99 method using the LOD as the tolerance estimated an 81 day WDI, the HLM method estimated a 96 day WDI.DiscussionThis study improves the understanding of the residue depletion kinetics of ivermectin in eggs after topical administration to older hens with inconsistent egg production. Ivermectin is systemically absorbed following topical administration of the injectable formulation in domestic egg laying chickens, resulting in prolonged egg residues. Ivermectin is preferentially distributed to the egg yolk over the egg white following topical administration of the injectable formulation in egg laying chickens. Since plasma kinetics were not evaluated, the impact of systemic exposure on egg residue kinetics following topical administration remains unknown. The results provide insight into how the estimated ivermectin egg WDIs using regulatory methods differ based on the maximum residue limit/tolerance applied and portion of the terminal elimination phase sampled.